Manajemen Yayasan Pendidikan Islam Dalam Pengembangan Sumber Daya Manusia Tenaga Pendidik Dan Kependidikan - Alam Harahap, Sori; Tanika, Gita (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
Foundation management is the key to the success of private educational institutions in developing madrasah both physically and non-physically. So that the institutions under its auspices are able to contribute to the growth of education in Indonesia. The management of the Islamic Education Foundation for the development of human resources for educators and education staff in madrasah in Tanah Merah sub-district, Indragiri Hilir Regency needs to be investigated so that it is known exactly how the steps and methods of development are appropriate for the progress of the foundation. Among the development methods used are on the job training and off the job training. Grouping on the job training (position rotation, training, guidance and counseling, job instruction exercises, demonstrations, and temporary assignments). Off the job training is divided into (courses, education, workshops, and seminars). This type of research is descriptive by using qualitative methods. This study uses data analysis techniques, namely data reduction (data reduction), data presentation (data display), and conclusions or verification (conclusion/verification). The management of the Kuala Enok Islamic Education Foundation has been good in the religious and social fields. However, there are some improvements that must be addressed immediately, namely in the aspect of fostering educators and education staff through training and development. The methods that have been applied are job rotation, get education from university, courses, workshops, KKG (teacher training) and seminars.